2021
DOI: 10.1063/5.0056183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fly ash on the self-healing capability of cementitious materials with crystalline admixture under different conditions

Abstract: The self-healing capability of cracks plays an important role in improving the durability of concrete. This study investigated the the self-healing capability of mortar with crystalline admixture and fly ash under three conditions. The compressive strength, water absorption, and surface crack pattern were used to evaluate self-healing capability of mortar, and the composition of the healing products was analyzed by x-ray diffraction and scanning electron microscopy. The results indicated that the crystalline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…al. [54] found that a 30% fly ash content and a 1.5% ICW content achieve 102% mechanical strength recovery under water immersion conditions. After water immersion, wet-dry cycles ensure the best self-healing performance.…”
Section: Resultsmentioning
confidence: 96%
“…al. [54] found that a 30% fly ash content and a 1.5% ICW content achieve 102% mechanical strength recovery under water immersion conditions. After water immersion, wet-dry cycles ensure the best self-healing performance.…”
Section: Resultsmentioning
confidence: 96%
“…Concrete has advantages including high compressive strength, easy to shape according to the needs of building structures, resistance to high temperatures, ease to obtain concrete constituent materials, especially in Indonesia, and low maintenance costs. Concrete also has drawbacks, namely workability and density to water (permeability) depending on the nature of the material, the formation of pores originating from the hydration process (water and cement), and the remaining water that evaporates in the concrete after the hydration process which causes the concrete to be impervious to water [7].…”
Section: Introductionmentioning
confidence: 99%